Некомутативна геометрія та застосування в астрофізиці - Moskaliuk, S.S.; Wohlgenannt, M. (Publishing house "Academperiodika", 2012)
We introduce basic concepts of noncommutative geometry and noncommutative topological quantum field theory (NC TQFT). Some approaches to noncommutative gravity are reviewed. Furthermore, we discuss some applications to astrophysics.